Diszharmónia, apokalipszis és hatalom - Farkas, Attila (Kultúratudományi Szemle, 2022)
Disharmony, apocalypse and power Attila Farkas In my writing, I reconstruct the historical steps of the development of a suboptimal equilibrium between nature and man, I consider the solidification of the password “Dominion over nature” as a result of misunderstandings, at the same time I also criticise the standpoint that the efforts made so far to create harmony between man and nature would have been in vain.